Resistive pulse sensing of magnetic beads and supraparticle structures using tunable pores - Willmott, Geoff R. (American Institute of Physics, 2012)
Tunable pores (TPs) have been used for resistive pulse sensing of 1 μm superparamagnetic beads, both dispersed and within a magnetic field. Upon application of this field, magnetic supraparticle structures (SPSs) were observed. Onset of aggregation was most effectively indicated by an increase in the mean event magnitude, with data collected using an automated thresholding method. Simulations enabled discrimination between resistive pulses caused by dimers and individual particles. Distinct but time-correlated peaks were often observed, suggesting that SPSs became separated in pressure-driven flow focused at the pore constriction. The distinct properties of magnetophoretic and pressure-driven transport mechanisms can explain variations in the event rate when particles move through an asymmetric pore in either direction, with or without a magnetic field applied. Use of TPs for resistive pulse sensing holds potential for efficient, versatile analysis and measurement of nano- and microparticles, while magnetic beads and particle aggregation play important roles in many prospective biosensing applications.